Rising Learners’ Awareness of National Identity through Literature The case of Third year LMD Students of English at Amar Telidji University -laghouat -2018/2019 - Zazaa ,Souad; Tahtah ,Dehaiba; Naoumi ,Mohamed (Faculty of Letters and Foreign Languages Department of English, 2019)
It is common sense that literature is a significant subject to be studied since it reflects every single aspect of human life. In this thesis, the research investigates the role of the literature in rising awareness among students. In relation to this, teaching literature remains a difficult task as course outline, teaching methods and objectives vary greatly from one teacher to another. The essential aim behind conducting this research is to show that literature is the best powerful tool to discovering new cultures. In specific; learners may explore new themes and topics through literary texts. In this study, the research describes the role of literature in depicting the importance of literary texts in rising learner’s awareness of national identity. To investigate the situation, this empirical study used questionnaire to the third year LMD students. All data obtained from the questionnaire are analyzed, interpreted and represented in form of tables and pie charts. The results show that literature can be helpful and considered as powerful tool that can change the society and helps learners to get familiar with different cultures, tradition and values. What is more, the present study provides some strategies, techniques and methods to teach the importance of national identity through literature .As expected, literature is the best way to raise awareness of national identity among students